THE EFFECT OF OPERATING CASH FLOW, NET PROFIT, ROA AND ROE ON STOCK RETURN OF IDX - Jessy Safitri Sitorus; Ernika Siburian; Yosevin Simbolon; Royto Enjelia br Naibaho (UNIB Press, 2021)
This research was conducted to determine the effect of Operating Cash Flow, ROA Net Profit and ROE on the movement of Stock Return, data or information obtained through financial statements. And the method of data collection is done with Purposive Sampling there are 21 companies in a period of 3 years, therefore the total sample of this study should be 63 samples. But because the data of this study using outliers then the total sample became 41. Then analyzed using multiple linear regression using SPSS 20 software. From this research, the researchers obtained results, namely: Operating Cash Flow, Net Income, and ROA individually had no significant effect on Stock Return. ROE individually affects and is significant to the Return of Shares. Operating Cash Flow, Net Income, ROA and ROE are simultaneously concurrently and significantly impacted on Stock Return. Keywords: Operating Cash Flow, Net Income, Return on Assets, Return on Equity, Share Return.